(untitled) (INMR - Innovation & Management Review, 2009)
The purpose of this paper is to contribute to the debate on how companies create organizational environments conducive to innovation development, through its culture, resources, competencies, and the use of interorganizational networks. These factors, as a set, are known as innovative capacity. To accomplish this goal, a bibliographic review theme is carried out, as well as an exploratory research, conducted by case study about the innovation management process in two companies, both considered innovative, and each belonging to a different industrial sector. An analysis of the results of the empirical study suggests that the building of innovative capacity can have different meanings in different types of companies that act in market segments featuring different levels of technology. A greater understanding of how the building of innovative capacity occurs across different industry sectors could assist companies in better allocation of their resources to leverage their innovative capacity, and therefore building sustainable competitive advantages.